2016
DOI: 10.1103/physrevlett.116.028101
|View full text |Cite
|
Sign up to set email alerts
|

How Internally Coupled Ears Generate Temporal and Amplitude Cues for Sound Localization

Abstract: In internally coupled ears, displacement of one eardrum creates pressure waves that propagate through air-filled passages in the skull and cause displacement of the opposing eardrum, and conversely. By modeling the membrane, passages, and propagating pressure waves, we show that internally coupled ears generate unique amplitude and temporal cues for sound localization. The magnitudes of both these cues are directionally dependent. The tympanic fundamental frequency segregates a low-frequency regime with consta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 14 publications
1
93
0
Order By: Relevance
“…Model simulations for internally coupled ears in vertebrates [36,37] have shown a similar functionality of internally connected ears, where coupling may enhance amplitude differences in the high-frequency range. We found that for the field cricket, directional sensitivity was not limited to the calling song frequency, but was rather broadly tuned, similar to observations in a tree cricket [33].…”
Section: Discussionmentioning
confidence: 99%
“…Model simulations for internally coupled ears in vertebrates [36,37] have shown a similar functionality of internally connected ears, where coupling may enhance amplitude differences in the high-frequency range. We found that for the field cricket, directional sensitivity was not limited to the calling song frequency, but was rather broadly tuned, similar to observations in a tree cricket [33].…”
Section: Discussionmentioning
confidence: 99%
“…As in any linear system with a periodic input, one can introduce impedances, complex numbers, as fit parameters but that is not an a-priori theory based on geometry and tympanic elasticity only. Based on the 2- and 3-dimensional wave equation that describe waves in the 3-dimensional air-filled cavity and with damping, which is important, in the 2-dimensional eardrums, Vossen et al (2010) and Vedurmudi et al (2016a) were the first to present a complete mathematical theory, the former focusing on lizards and the latter encompassing the characteristics of all terrestrial vertebrates with ICE. It turns out that the 3-dimensional geometry plays a remarkable, unforeseen, role; for details including the key role played by the tympanic fundamental frequency, we refer to Vedurmudi et al (2016b).…”
Section: Intermezzomentioning
confidence: 99%
“…Small creatures such as flies and lizards are known to possess the capability of accurately sensing the angle of an incident sound wave whose wavelength is much larger than their physical dimensions. Such an exotic characteristic in these small creatures has inspired miniature directional sensors both in optics and acoustics . The mechanisms behind the subwavelength directional sensing are explained with coupled resonances that amplify acoustic energy stored in each resonance.…”
Section: Introductionmentioning
confidence: 99%
“…For example, miniature MEMS directional sound sensors mimic the Ormia ochracea fly's hearing system where two eardrums of the fly are mechanically coupled, supporting dual vibration modes sensitive to the incident angle . Moreover, for small animals (lizards), subwavelength sensing employs dipolar resonances through the two internally coupled eardrums (membranes) that permit instantaneous pressure difference across the membrane . Despite their promising performance, the bioinspired directional sensors based on such an internal coupling or structurally coupled resonators pose challenges associated with dedicated sensing components and a limited sensing range (i.e., from 0° only up to 180°).…”
Section: Introductionmentioning
confidence: 99%